Desenvolvimento de géis-creme a partir do produto liofilizado contendo nanocápsulas de óleo de borragem e dipropionato de betametasona - Bazana, Maiara Taís (2015)
Among skin diseases, atopic dermatitis is characterized as a chronic inflammatory, it is widely used corticosteroids, including betamethasone dipropionate. Allied to this, Borago officinalis L. seed oil has fatty acids important in the structure and function of the skin. Thus, with the use of nanotechnology and lyophilization it is possible to improve some properties of substances and developing innovative effective therapies. Therefore, this study aimed to develop cream gels from the lyophilized product of lipid-core nanocapsules suspensions containing the oil of the Borago officinalis L. (borage oil) associated or not with betamethasone dipropionate drug, for their application in the treatment inflammatory skin diseases. The nanocapsules suspension were prepared by the interfacial of the preformed polymer method, and after characterization, dehydrated by lyophilization. Dehydrated products were evaluated relative to the yield, mean particle size after redispersion in water, the particle size distribution, drug content, resuspension index, morphological analysis and in vitro drug release. Furthermore, the preparation and characterization of cream gels were made, followed by an in vitro drug permeation study based on semi-solid formulations and the evaluation of the efficacy in an experimental model of contact dermatitis. The suspensions showed nanometric particle size (185-210 nm) polydispersion index below 0.10, slightly acidic pH (6.0-6.5), absence of nanocrystals and distribution of the drug in the core. The drug content was 0.25 ± 0.01 mg mL-1 betamethasone, and the encapsulation efficiency was approximately 100%. For lyophilization, the dehydrated products had particle size in the nanometer range (190-250 nm), polydispersity below 0.35, resuspension index close to unity, yield around 93% and the concentration of betamethasone close to theoretical. The release profile of betamethasone dipropionate from nanocapsules and redispersed products presented control the release and monoexponential model. The cream gels presented pH (6.0-6.5) and drug content close to the theoretical (0.5 mg / g). Rheograms exhibited non-Newtonian flow behavior, following the model of Herschel-Bulkley. In vitro skin permeation/penetration indicated that betamethasone dipropionate is capable of achieving the different skin layers, however, cream gels not associated with drug was detected in the receptor medium. For efficacy in vivo, contact dermatitis model was capable of causing tissue damage with changes in enzyme activities of the purinergic system. Among the different treatments, cream gels containing borage oil and betamethasone dipropionate nanostructures with alternating treatment showed the best dermatological efficacy, immunological and reduced oxidative damage in tissues evaluated.